Communal breeding affects offspring behaviours associated with a competitive social environment. Issue 1 (December 2018) - Fischer, Stefan; Pujol, Neus; Bolton, Rhiannon; Hurst, Jane; Stockley, Paula
Abstract Communal breeding is characterised by shared care of offspring produced by more than one female, and can affect the behavioural development of young. The decision to care communally can vary according to local conditions, and has been hypothesised to occur more frequently when social competition is intense. However, it is unknown whether communal rearing of young influences adult behaviours likely to be adaptive under competitive conditions. Here, using a controlled experimental approach, we investigate effects of communal rearing on competitive and exploratory behaviours of adult male house mice. In tests of competitive scent marking, only communally-reared subjects discriminated between related and unrelated rivals, depositing more scent marks in close proximity to unrelated males. Communally-reared subjects also displayed higher exploratory tendencies, with an increased probability of crossing a water barrier, while not exhibiting higher activity levels in an open field test. Since exploration tendencies and discrimination between kin and non-kin are likely to be advantageous when dispersing from the natal territory or in a high density population, our findings suggest that communal rearing prepares male house mice for a competitive social environment. Our results add to growing evidence that the early social environment influences development of important behavioural competences to cope with social challenges later in life.